Derrida and deconstruction - Silverman, Hugh J. (Continental philosophy, 1989)
The effects of Derrida's writings have been widespread in literary circles, where they have transformed current work in literary theory. By contrast Derrida's philosophical writings--which deal with the whole range of western thought from Plato to Foucault--have not received adequate attention by philosophers. Organized around Derrida's readings of major figures in the history of philosophy, Derrida and Deconstruction focuses on and assesses his specifically philosophical contribution. Contemporary continental philosophers assess Derrida's account.